Симуляція процесу руйнування зерна ударним різанням - Алієв, Ельчин Бахтияр огли; Aliiev, Elchyn; Білоус, Ілля Михайлович; Bilous, Illia (Центральноукраїнський національний технічний університет, 2025)
У статті досліджено вплив конструктивних та кінематичних параметрів нового робочого органу дискового подрібнювача з ударними накладками на процес руйнування зерна кукурудзи, пшениці та ячменю методом ударного різання. Моделювання проведено із використанням методу дискретних елементів (DEM) у середовищі Simcenter STAR-CCM+. Встановлено залежності сили руйнування від відстані між накладками, кута їх розміщення та лінійної швидкості руху. Запропоновано інтегральний критерій ефективності, що дозволяє оптимізувати параметри подрібнення для досягнення енергоощадного та продуктивного режиму роботи. Визначено раціональні значення конструктивних параметрів для ефективного подрібнення основних зернових культур. The aim of the research is to perform numerical modeling of the concentrated feed grinding process and to determine the influence of the physical and mechanical properties of the grain, its orientation, and the parameters of the disc crusher on the fracture force during impact cutting. Considering the specific design of the new working unit of the disc crusher with impact inserts, the influence of three key factors – distance between impact inserts (l), angle between them (α), and the linear velocity of insert motion (V) – was investigated through numerical simulation of the grain fracture process for corn, wheat, and barley using the discrete element method (DEM) in the Simcenter STAR-CCM+ environment. The patterns of fracture force for corn, wheat, and barley grains under three orientations during impact cutting were established depending on the distance between inserts, the angle between them, and the linear velocity. The identified patterns provide a quantitative assessment and a deeper physical understanding of the grain shell destruction processes under impact cutting conditions. This serves as a basis for optimizing the design parameters of the crusher to enhance the efficiency and energy savings in processing different types of grain materials. To comprehensively evaluate the grain grinding process, an integral efficiency criterion was proposed, aiming to minimize fracture force at maximum distance between inserts and minimum insert speed. This allows for high process productivity while simultaneously reducing kinetic energy consumption. Rational grinding parameters were established for the main cereal crops – corn, wheat, and barley. The analysis of the obtained results confirms that the process parameters (distance between inserts l = 1.68–1.79 mm, installation angle β = 21.8–25.3°, insert velocity V = 4.72–5.86 m/s, disk rotation speed n = 1503–1865 rpm, modular clearance δ = 0.68–0.79 mm) reflect the physical and mechanical characteristics of each crop.
Simulation of the Grain Destruction Process by Impact Cutting
Keywords: дисковий подрібнювач; disc crusher; ударні накладки; impact inserts; метод дискретних елементів; discrete element method (DEM); Simcenter STAR-CCM+; ударне різання; impact cutting; руйнування зерна; grain destruction; конструктивні параметри; design parameters; оптимізація; optimization; енергоефективність; energy efficiency